Competitive Advantage of Alfamart: A SWOT and PESTEL Analysis - Yusan, Budi Oktavianus; Trisandy, Yudhi; Lu, Cen; Saragih, John Salmar; Tjandrasa, Benny Budiawan (Yayasan Inspirasi Merah Putih Indonesia, 2025)
The Indonesian minimarket sector is undergoing rapid transformation, driven by intensified competition, decentralization, and digital disruption. This study investigates the competitive advantage of Alfamart, a leading minimarket chain in Indonesia, by employing an integrative SWOT and PESTEL framework. Using a qualitative case study approach—including interviews, surveys, and observational data—the research identifies key internal strengths such as store network scale, brand loyalty, and digital initiatives like Alfagift, alongside weaknesses including operational cost rigidity and limited pricing flexibility. The analysis reveals external opportunities in scalable franchising and rising consumer demand for health-oriented retail, while highlighting threats from regulatory restrictions and digital-native competitors. The findings position Alfamart in an aggressive strategy quadrant, emphasizing the importance of aligning internal capabilities with macro-environmental dynamics. The study concludes that strategic agility is essential for sustaining competitiveness in a decentralized and digitally disrupted market. Limitations include qualitative scope and a localized sample, with future research recommended to explore broader demographics and predictive modeling.